Hypothetical Learning Trajectory in Scientific Approach on Material Direct Proportion: Context of Rice Farmers' Activities Pandanwangi Cianjur - Sugiarni, Rani; Herman, Tatang; Juandi, Dadang; Supriyadi, Edi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Rice farmer activities can be used as a context for understanding mathematical concepts. There are many studies on Hypothetical Learning Trajectory (HLT) on direct proportion material with a cultural context background. However, there is no research that focuses on using the context of Pandanwangi rice farmers to facilitate students in understanding material in direct proportion.This study aims to design Hypothetical Learning Trajectory (HLT) in Scientific Approach on Material Direct Proportion in the Context of Rice Farmers' Activities in Pandanwangi Cianjur, who are familiar with student culture in Cianjur. This research is part of design research. The research design consisted of HLT, namely learning objectives, learning activities, and student learning hypotheses. The result of the research is the set of HLT in the context of Pandanwangi Rice Farmer Activities, which includes learning objectives, learning activities, and the assumptions of each activity. This HLT can be a promising solution to overcome students' difficulties in understanding the concept of direct proportion and values in a cultural context to improve students' character.